2020
DOI: 10.18632/aging.103530
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation-mediated degradation of HSD17B4 regulates the progression of prostate cancer

Abstract: Steroidogenic enzymes are crucial in prostate cancer (PCa) progression. 17β-Hydroxysteroid dehydrogenase type 4 (HSD17B4), encoded by HSD17B4, lacks catalytic capacity in androgen metabolism. Now the detailed role and molecular mechanism of PCa development are largely unknown. Here we showed that the expression of HSD17B4 was increased in PCa tissues compared to paired paratumor tissues. HSD17B4 knockdown in PCa cells significantly suppressed its proliferation, migration and invasion, while overexpressing HSD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Several studies have demonstrated that phosphatidylserine (PS) can bind to D-bifunctional protein (D-BP) and localize to peroxisomes, implying that PS can also affect the β-oxidation process [123]. It is worth noting that some studies have pointed out that acetylation is important for the normal functioning of D-BP [124,125], but related studies are not common; thus, we do not know which factors affect its acetylation process. Another key regulatory enzyme of peroxisomal β-oxidation, Acetyl-CoA acyltransferase 1 (ACAA1), has been extensively studied.…”
Section: Othersmentioning
confidence: 99%
“…Several studies have demonstrated that phosphatidylserine (PS) can bind to D-bifunctional protein (D-BP) and localize to peroxisomes, implying that PS can also affect the β-oxidation process [123]. It is worth noting that some studies have pointed out that acetylation is important for the normal functioning of D-BP [124,125], but related studies are not common; thus, we do not know which factors affect its acetylation process. Another key regulatory enzyme of peroxisomal β-oxidation, Acetyl-CoA acyltransferase 1 (ACAA1), has been extensively studied.…”
Section: Othersmentioning
confidence: 99%
“…37 Hsd17b4 is involved in the catabolism of fatty acids and steroid hormones, and various studies have revealed Hsdl7b4 to be implicated in the development of prostate and breast cancer. 38 , 39 Hsd17b4 is linked to the peroxisome, which catalyzes many critical metabolic activities, primarily related to lipid metabolism. Obesity alters peroxisome function, resulting in aberrant lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was reported that HSD17B4 (hydroxysteroid 17-beta dehydrogenase 4) overexpression promotes proliferation and malignancy of prostate cancer cells. Acetylation of HSD17B4 promotes its degradation by CMA and leads to a subsequent decrease in prostate cancer progression [ 98 ]. In this case, autophagy does not participate in cell death, but leads to degradation of a factor that enhances prostate cancer progression.…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%